Amino Acid Assisted One‐Pot Green Synthesis of N‐Doped 3D Graphene for Ultrasensitive Neurochemical Sensing. Issue 44 (24th November 2020) - Zhang, Minwei; Wanfeng, Wu; Chen, Fei; Zhang, Wenrui; Halder, Arnab
Abstract: Graphene is undoubtedly one of the most promising materials in the last decade due to its outstanding physicochemical properties. However, in order to use graphene for diverse electrochemical or device‐based applications, it is mandatory to tune its electronic properties through doping. 3D graphene is three‐dimensional structural arrangement of its 2D sheets. In this work, we have explored a simple, one‐pot hydrothermal reaction approach to synthesize nitrogen doped 3D graphene (3D N‐RGO) structure by using graphene oxide (GO) as raw material and amino acids as nitrogen doping agent. Twenty different amino acids were individually used as doping agents and each of their nitrogen doping ability in graphene were carefully analyzed by using x‐ray photoelectron spectroscopic (XPS) analysis. The results demonstrated that a great majority of amino acids can enable nitrogen doping except for tyrosine and phenylalanine whose ‐R group has benzene group. Among others, lysine, histidine, tryptophan and proline have relatively higher doping amount of nitrogen compared with others. Lysine has shown the highest doping efficiency. Furthermore, lysine induced 3D N‐RGO was used for proof‐of‐concept electrochemical sensing of neurochemical dopamine with a lower limit of detection of 2.8 μM and high sensitivity of 40.81 mA mM −1 . Abstract : Twenty different amino acids were used as doping agent and graphene oxide (GO) as raw material to obtain 3D N‐RGO via a simple one‐step hydrothermal way as well as research the effect of various amino acid on GO. From all the results, we can know that whole amino acids can work except tyrosine and phenylalanine whose R group has benzene group; among them, lysine has the highest doping amount of nitrogen, and 3D N‐RGO with special structure could also application for detection of neurochemical dopamine.